The Measurements of Calcification Rates in Reef Corals Using Radioisotope 45Ca at Pongok Sea, South Bangka - G. Diansyah; TZ. Ulqodry; M. Rasyid; A. Djawanas (PPIKSN-BATAN, 2011)
Coral reef ecosystem is one of the most important ecological systems in the Indonesian coastal zone. The aim of this study which was undertaken between August - October 2006, is to measure the calcification of corals in a reef coral in the Pongok Sea, South Bangka using 45Ca. The steps in conducting this study were surveying of the site, preparation, transplanting, incubation in the 45Ca - solution, and analysis of the coral fragments. The results showed that at the depth of 5 m different counts per minute (cpm) trend occurred. For the samples taken from the transplantation of the Artificial Colony (Ac) the cpm showed that with the progress of time the cpm declined, reaching its lowest cpm at 5 hours after retransplanting of the coral fragments. On the other hand the samples obtained from the natural (Nc) colony showed that the cpm increased with time progress. At the 10 m depth where only the coral fragment of the natural colony (Nc) was observed a different pattern showed up. Here with the progress of time up to 3 hours the cpm increased and after that it declined to reach a low cpm at 5 hours of observation. The cpm values were then transformed to disintegrations per minute (dpm), μCi and at the end to 45Ca content. The same trend is shown for dpm, μCi/0.5 g sample and μg Ca/0.5 g sample. The 45Ca content (μg/0.5g sample) were used to show the calcification rates of coral fragments. It showed clearly that 45Ca could be used to calculate the magnitude of calcification. Received: 08 December 2009; Revised: 05 April 2011; Accepted: 05 April 2011